Sodium ferric pyrophosphate positive electrode material and preparation method thereof

By simplifying the process flow and reducing energy consumption, the sodium iron phosphate pyrophosphate positive electrode material is prepared, which solves the problems of cumbersome preparation process, high energy consumption and poor phase optimization in the existing technology, and achieves efficient preparation of the material and improves electrochemical performance.

CN119920899AActive Publication Date: 2025-05-02SOUTHWEAT UNIV OF SCI & TECH

Patent Information

Application Number
CN202510079586.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-18
Publication Date
2025-05-02
Estimated Expiration
2045-01-18

AI Technical Summary

Technical Problem

The existing preparation methods of sodium ferric phosphate cathode material have problems such as cumbersome production process, high energy consumption and poor phase optimization, which affects the electrochemical performance and cost advantages of the material.

Method used

A soluble compound composition containing an iron source, a sodium source, a phosphorus source, and a carbon source is dissolved in deionized water to form a precursor solution, and a strongly absorbent organic solvent is added, and a sodium iron pyrophosphate positive electrode material is obtained by high temperature sintering. This method simplifies the process flow, reduces energy consumption, and optimizes the heterogeneous phase generation by adjusting the proportion of raw materials.

Benefits of technology

The efficient preparation of sodium iron phosphate pyrophosphate positive electrode material is achieved, which reduces production costs, improves the electrochemical performance of the material, solves the miscellaneous phase problems, and enhances the competitive advantage of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920899A_ABST
    Figure CN119920899A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ferric pyrophosphate positive electrode material and a preparation method thereof, and belongs to the technical field of sodium ion battery positive electrode material synthesis, the molecular formula of the sodium ferric pyrophosphate positive electrode material is Na < 3.6 > Fe < 2.6 > (PO4) < 1.6 > P2O7; the preparation method of the sodium ferric pyrophosphate positive electrode material comprises the following steps: S1, dissolving a soluble compound composition containing an iron source, a sodium source, a phosphorus source and a carbon source in deionized water to form a precursor solution, and stirring until the precursor solution is uniform; s2, adding the precursor solution into a strong water-absorbing organic solvent of which the volume is 1-4 times that of the precursor solution, fully stirring to separate out a precursor, and then filtering under reduced pressure to obtain a precursor with uniformly distributed elements; and S3, sintering the precursor at high temperature to obtain the sodium ferric pyrophosphate positive electrode material. According to the invention, while the preparation process of the sodium ferric pyrophosphate material is greatly simplified, the excellent electrochemical performance of the sodium ferric pyrophosphate material is ensured, and the problems of tedious production process, high energy consumption and poor impurity phase optimization in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthesis of positive electrode materials for sodium ion batteries, and in particular to a sodium iron pyrophosphate positive electrode material and a preparation method thereof. Background Art

[0002] As lithium-ion batteries face increasing challenges in terms of safety, cost, and resource acquisition, researchers are working to develop a new generation of low-cost and safe energy storage technologies. In this context, sodium-ion batteries have received widespread attention. Sodium-ion batteries and lithium-ion batteries work on the same principle, but compared with lithium-ion batteries, sodium-ion batteries have cost advantages, excellent rate performance, outstanding safety performance, and a wide operating temperature range. More importantly, sodium resources are widely available and not restricted by geographical location, and the price is low and stable, so it is expected to become an effective alternative to lithium-ion batteries.

[0003] At present, the positive electrode materials of sodium-ion batteries are mainly divided into three categories: layered transition metal oxides, polyanionic compounds and Prussian blue compounds. Among them, layered transition metal oxides have developed slowly due to their poor stability in the air, and Prussian blue compounds have developed slowly due to the difficulty of water removal process; while polyanionic compounds have shown great energy storage potential because of their outstanding structural stability and long cycle life.

[0004] For polyanionic compounds, taking sodium iron pyrophosphate as an example, it has become the main hot material in current research because of its small volume change during sodium insertion and extraction, environmental friendliness, low cost, moderate operating voltage and high discharge specific capacity.

[0005] In the prior art, the preparation of sodium iron pyrophosphate positive electrode materials mainly has the following two problems:

[0006] First, the preparation methods mainly include ball milling solid phase synthesis, sand milling-spray drying liquid phase synthesis, freeze drying synthesis and sol-gel synthesis. However, the huge energy consumption, complicated production process and equipment requirements brought about by these methods in generating precursors have increased the cost of material production, which is undoubtedly contrary to the price advantage of sodium-ion batteries.

[0007] For example, Patent Publication No.: CN116344823A discloses a carbon-coated composite material and its preparation method and application (hereinafter referred to as "prior art 1"), which adopts sand milling-spray drying liquid phase synthesis precursor (that is, wet sand milling is used to produce precursor slurry, and then spray drying is used to evaporate the highly water-absorbent organic solvent to obtain the precursor). Its production cycle is long and the energy consumption is huge.

[0008] Second, the sodium iron pyrophosphate phosphate cathode material produced by conventional stoichiometry inevitably contains Na 2 FeP 2 O 7 and m-NaFePO 4 heterophase, which undoubtedly affects the electrochemical performance of the material. Although the prior art 1 uses a method of reducing the iron content in sodium iron pyrophosphate phosphate to reduce the NaFePO 4 heterophase, it uses a defect-like idea, and the entire adjustment process does not satisfy charge conservation, that is, Na 4 Fe 3-x (PO 4 ) 2 P 2 O 7 (0 < x < 0.15), so the optimization of the heterophase is relatively one-sided, and the situations at both ends of Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 and Na 3 Fe 2 (PO 4 )P 2 O 7 are not considered.

[0009] In summary, it is necessary for those skilled in the art to improve the existing preparation method of sodium iron pyrophosphate phosphate cathode material, so that it not only has the characteristics of high synthesis efficiency, low synthesis energy consumption, and simple synthesis equipment, but also can solve the problem of heterophase, thereby fully improving the competitive advantage of sodium iron pyrophosphate phosphate in sodium-ion batteries. Summary of the Invention

[0010] The purpose of the present invention is to provide a sodium iron pyrophosphate phosphate cathode material and a preparation method thereof, which solve the problems of cumbersome production process, high energy consumption, and poor heterophase optimization existing in the prior art.

[0011] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0012] One of the purposes of the present invention is to provide a sodium iron pyrophosphate phosphate cathode material, and the molecular formula of the sodium iron pyrophosphate phosphate cathode material is Na 3.6 Fe 2.6 (PO 4 ) 1.6 P 2 O 7 .

[0013] Another purpose of the present invention is to provide a method for preparing the above-mentioned sodium iron pyrophosphate phosphate cathode material, including the following steps:

[0014] Step S1, dissolving a soluble compound containing an iron source, a sodium source, a phosphorus source, and a carbon source in deionized water to form a precursor solution with a concentration of 0.2-2.4 mol / L, and stirring until uniform; the stoichiometric ratio of the sodium source, the iron source, the phosphorus source, and the carbon source in the soluble compound is 1.33-1.50:1:1.33-1.50:1.33-1.50;

[0015] Step S2, adding the precursor solution into 1-4 times the volume of a strongly water-absorbing organic solvent, stirring thoroughly to precipitate the precursor, and then filtering under reduced pressure to obtain a precursor with uniform element distribution;

[0016] Step S3: sintering the precursor at high temperature to obtain sodium iron pyrophosphate positive electrode material.

[0017] Preferably, the concentration of the precursor solution is 1.2 mol / L.

[0018] Specifically, the soluble compound composition includes the following substances in a molar ratio:

[0019] first soluble compound 2-3;

[0020] The second soluble compound 3-4;

[0021] The third soluble compound 3-4.

[0022] Preferably, the first soluble compound is one or more of ferric citrate, ferric acetylacetonate, ferric nitrate, ferrous sulfate and ferric hydroxide.

[0023] Preferably, the second soluble compound is one of sodium hydroxide, sodium carbonate, sodium acetate, sodium nitrate, sodium nitrite, sodium dihydrogen phosphate, disodium hydrogen phosphate, phosphoric acid, diammonium hydrogen phosphate, and sodium pyrophosphate, which contains both a sodium source and a phosphorus source, or a combination of two or more substances containing both a sodium source and a phosphorus source.

[0024] Preferably, the third soluble compound is one or more of soluble starch, citric acid, grape, sucrose and maltose.

[0025] Preferably, the strongly water-absorbing organic solvent is one or more of ethylene glycol, propylene glycol, N-methylpyrrolidone and dimethylacetamide.

[0026] Preferably, in step S2, the precursor solution is added into 2.5 times the volume of a strongly water-absorbing organic solvent.

[0027] Specifically, step S3 includes the following steps:

[0028] Step S301, pre-calcining the precursor at 300° C.-350° C. in an inert atmosphere for 5-6 hours to obtain an intermediate product;

[0029] Step S302: calcining the intermediate product at 500° C.-550° C. in an inert atmosphere for 15-18 hours to obtain a sodium iron pyrophosphate positive electrode material.

[0030] The design principle of the present invention is:

[0031] First, the iron source, sodium source, phosphorus source, and carbon source are dissolved in deionized water to form a precursor solution, and then a strongly hygroscopic organic solvent is added. The hydrogen bond interaction between polar groups such as carbonyl (C=O) and hydroxyl (-OH) in the organic solvent and water molecules is used to form a hydrogen bond complex between the organic solvent and water, so that the precursor and water are separated, and finally a precursor with uniform element distribution is obtained. In this way, after high-temperature sintering, the established sodium iron pyrophosphate positive electrode material, namely: Na 3.6 Fe 2.6 (PO 4 ) 1.6 P 2 O 7 .

[0032] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0033] (1) Based on the difference in the preparation system, the organic solvent used in the present invention has a different main function from the existing process, such as the organic solvent used in the scheme recorded in the above patent publication number: CN116344823A. The organic solvent in the present invention has the function of absorbing water, forming a hydrogen bond complex, and separating the precursor from the water; while the main function of the organic solvent in CN116344823A is to disperse, as a dispersion medium for sand milling, and there is no change before and after use. Therefore, the present invention, through the selection of raw materials and process design, is compared with the existing methods such as ball milling solid phase synthesis, sand milling-spray drying liquid phase synthesis, freeze drying synthesis and sol-gel synthesis. Not only is the preparation process of the precursor simpler, the cycle is short, and the energy consumption is low, but also the elements in the precursor are evenly distributed, and the product quality after high-temperature sintering can also be guaranteed. Experiments show that the electrochemical properties of the sodium iron pyrophosphate positive electrode material obtained therefrom are improved to a certain extent compared with the electrochemical properties of the conventionally produced materials.

[0034] (2) The ratio of sodium source to iron source in the raw material is designed in the present invention, which effectively reduces the Na 2 FeP 2 O 7 Mixed phase or m-NaFePO 4 The generation of impurity phase, its regulation process always satisfies the charge conservation, and fully considers the Na4 Fe 3 (PO 4 ) 2 P 2 O 7 and Na 3 Fe 2 (PO 4 ) 2 O 7 The two endpoints make the optimization of the impurity phase more comprehensive, which can more effectively improve the electrochemical performance of the sodium iron pyrophosphate positive electrode material and enhance the competitive advantage of the sodium iron pyrophosphate material for sodium ion batteries.

[0035] (3) The various links of the present invention are closely linked, complementary and related to each other. While greatly simplifying the preparation process of the sodium iron pyrophosphate material, it also ensures that the sodium iron pyrophosphate material has excellent electrochemical properties. Therefore, the present invention is very suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a schematic diagram of the process for preparing sodium iron pyrophosphate material according to Example 1 of the present invention.

[0037] Figure 2 This is the XRD spectrum of the sodium iron pyrophosphate material prepared in Examples 1-3 of the present invention.

[0038] Figure 3 This is a charge and discharge curve diagram of the sodium iron pyrophosphate material prepared in Examples 1-3 of the present invention.

[0039] Figure 4 XRD patterns of the sodium iron pyrophosphate materials prepared in Example 3 and the comparative example of the present invention.

[0040] Figure 5 The first charge and discharge curves of the sodium iron pyrophosphate material prepared in Example 3 of the present invention and the comparative example at 0.1C.

[0041] Figure 6 It is a magnification diagram of the sodium iron pyrophosphate material prepared in Example 3 of the present invention and the comparative example.

[0042] Figure 7 Schematic diagram of 200 cycles of the sodium iron pyrophosphate material prepared in Example 3 of the present invention and the comparative example at 1C. DETAILED DESCRIPTION

[0043] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with various embodiments.

[0044] Example 1

[0045] This embodiment provides a sodium iron pyrophosphate material with a molecular formula of Na 3.6 Fe 2.6 (PO 4 ) 1.6 P 2 O 7 , prepared by precursor preparation + high temperature sintering, the entire preparation process is as follows Figure 1 shown.

[0046] The above process is described in detail below.

[0047] 1. Precursor preparation

[0048] The preparation of the precursor is one of the main inventive points of this embodiment, and its characteristics are simple process, high efficiency and low energy consumption. The specific process is as follows:

[0049] First, a soluble compound containing an iron source, a sodium source, a phosphorus source, and a carbon source is dissolved in deionized water to form a precursor solution, and then stirred until uniform. The soluble compound in this embodiment is composed of 0.2 mol of ferric nitrate, 0.3 mol of sodium dihydrogen phosphate, and 0.3 mol of citric acid, wherein the stoichiometric ratio of the sodium source, the iron source, the phosphorus source, and the carbon source is 1.50:1:1.50:1.50. The concentration of the formed precursor solution is 1.2 mol / L.

[0050] Next, the precursor solution is added into 3 times the volume of ethylene glycol, stirred for 1-2 hours to allow the precursor to be fully precipitated, and then filtered through a reduced pressure funnel to obtain a precursor with uniform element distribution.

[0051] 2. High temperature sintering

[0052] The high-temperature sintering of this embodiment is divided into two steps: pre-firing and calcination. The first is pre-firing: the precursor is pre-firing at 300°C in an inert atmosphere for 5 hours to obtain an intermediate product; then the calcination is performed: the intermediate product is pre-firing at 500°C in an inert atmosphere for 15 hours to obtain the final sodium iron pyrophosphate material.

[0053] Example 2

[0054] The difference from Example 1 is that in this embodiment:

[0055] 1. The soluble chemical composition is composed of 0.3 mol of ferric nitrate, 0.4 mol of sodium dihydrogen phosphate and 0.4 mol of citric acid, wherein the stoichiometric ratio of the sodium source, the iron source, the phosphorus source and the carbon source is 1.33:1:1.33:1.33.

[0056] 2. Add the precursor solution to 2.5 volumes of propylene glycol.

[0057] Example 3

[0058] The difference from Example 1 is that in this embodiment:

[0059] 1. The soluble compound composition is composed of 0.26 mol of ferric nitrate, 0.36 mol of sodium dihydrogen phosphate and 0.36 mol of citric acid, wherein the stoichiometric ratio of the sodium source, the iron source, the phosphorus source and the carbon source is 1.38:1:1.38:1.38.

[0060] 2. Add the precursor solution into 2.5 times the volume of N-methylpyrrolidone.

[0061] Example 4

[0062] The difference from Example 1 is that in this embodiment:

[0063] 1. The soluble compound composition is composed of 0.26 mol of ferric nitrate, 0.36 mol of sodium dihydrogen phosphate and 0.36 mol of citric acid, wherein the stoichiometric ratio of the sodium source, the iron source, the phosphorus source and the carbon source is 1.38:1:1.38:1.38. The concentration of the formed precursor solution is 0.6 mol / L.

[0064] 2. Add the precursor solution into 2.5 volumes of dimethylacetamide.

[0065] 3. During high-temperature sintering, the precursor is pre-sintered at 300°C in an inert atmosphere for 5 hours to obtain an intermediate product; then calcination is performed: the intermediate product is pre-sintered at 550°C in an inert atmosphere for 18 hours to obtain the final sodium iron pyrophosphate material.

[0066] Example 5

[0067] The difference from Example 1 is that in this embodiment:

[0068] 1. The soluble compound composition is composed of 0.26 mol of ferric nitrate, 0.36 mol of sodium dihydrogen phosphate and 0.36 mol of citric acid, wherein the stoichiometric ratio of the sodium source, the iron source, the phosphorus source and the carbon source is 1.38:1:1.38:1.38. The concentration of the formed precursor solution is 1.8 mol / L.

[0069] 2. Add the precursor solution into a mixed solvent of 2.5 times the volume of ethylene glycol and N-methylpyrrolidone.

[0070] 3. During high-temperature sintering, the precursor is pre-sintered at 350°C for 6 hours in an inert atmosphere to obtain an intermediate product; then calcined: the intermediate product is pre-sintered at 500°C for 15 hours in an inert atmosphere to obtain the final sodium iron pyrophosphate material.

[0071] Example 6

[0072] The difference from Example 1 is that in this embodiment:

[0073] 1. The soluble compound composition is composed of 0.26 mol of ferric nitrate, 0.36 mol of sodium dihydrogen phosphate and 0.36 mol of citric acid, wherein the stoichiometric ratio of the sodium source, the iron source, the phosphorus source and the carbon source is 1.38:1:1.38:1.38. The concentration of the formed precursor solution is 2.4 mol / L.

[0074] 2. Add the precursor solution into a mixed solvent of ethylene glycol and propylene glycol with a volume of 2.5.

[0075] 3. During high-temperature sintering, the precursor is pre-fired at 350°C for 6 hours in an inert atmosphere to obtain an intermediate product; then calcination is performed: the intermediate product is pre-fired at 550°C for 18 hours in an inert atmosphere to obtain the final sodium iron pyrophosphate material.

[0076] Comparison example

[0077] The control example adopts the spray drying method to prepare the sodium iron pyrophosphate material (Na 3.6 Fe 2.6 (PO 4 ) 1.6 P 2 O 7 ), the specific process is as follows:

[0078] Step 1: Weigh 0.26 mol of ferric nitrate, 0.36 mol of sodium dihydrogen phosphate and 0.36 mol of citric acid and dissolve them in deionized water to form a precursor solution with a concentration of 1.2 mol / L, and then stir until uniform, wherein the stoichiometric ratio of the sodium source, the iron source, the phosphorus source and the carbon source is 1.38:1:1.38:1.38;

[0079] Step 2: spray drying the precursor solution through a spray dryer to obtain a precursor;

[0080] Step 3: Sinter the precursor in two steps at 300°C and 500°C in an inert atmosphere to obtain the sodium iron pyrophosphate positive electrode material, with a pre-sintering time of 5 h and a calcination time of 15 h.

[0081] The relevant experimental conditions and conclusions of the above-mentioned Examples 1-6 and the comparative example are introduced below.

[0082] 1. Experimental results and conclusions of Examples 1-3 and Control Examples

[0083] 1. According to Figure 2It can be seen that in Examples 1-3, by properly adjusting the sodium iron ratio in the precursor, the obtained sodium iron pyrophosphate positive electrode material impurity phase is significantly reduced, wherein Example 3 does not have Na near 10.7° compared to Example 1. 2 FeP 2 O 7 Miscellaneous peaks; Compared with Example 2, there is no m-NaFePO near 33° 4 There are no impurity peaks, and the remaining diffraction peaks of Example 3 correspond one to one with the standard card, which indicates that the sodium iron pyrophosphate positive electrode material prepared in Example 3 has a higher phase purity.

[0084] 2. According to Figure 3 It can be seen that Example 3 has the highest discharge specific capacity and the most ideal charge-discharge curve compared to Example 1 and Example 2, which indicates that the capacity of the material is improved due to the reduction of impurities.

[0085] 3. In Example 3 and the comparative example, there is no difference in crystal structure between the sodium iron pyrophosphate positive electrode material prepared in Example 3 and the sodium iron pyrophosphate positive electrode material prepared by conventional spray drying. Figure 4 As shown, each diffraction peak corresponds to the standard card one by one, and there is no impurity peak.

[0086] 4. According to Figure 5 It can be seen that in Example 3 and the control example, the discharge specific capacity of the sodium iron pyrophosphate positive electrode material prepared in Example 3 is slightly higher than that of the sodium iron pyrophosphate positive electrode material prepared by conventional spray drying.

[0087] 5. According to Figure 6 , Figure 7 It can be seen that in Example 3 and the control example, there is no difference in rate performance and cycle performance between the sodium iron pyrophosphate positive electrode material prepared in Example 3 and the sodium iron pyrophosphate positive electrode material prepared by conventional spray drying.

[0088] II. Experimental results of different precursor solution concentrations in Examples 3-6

[0089] In Examples 3-6, the optimal solution concentration was obtained by exploring the concentration of the precursor solution. As shown in Table 1, when the concentration of the precursor solution was below 1.2 mol / L, the capacity of the prepared materials was 112 mAh·g -1 When the concentration of the precursor solution exceeds 1.2 mol / L, the capacity of the prepared material decreases (Examples 5-6).

[0090] Table 1 Na prepared in Examples 3-6 3.6 Fe 2.6 (PO 4 )1.6 P 2 O 7 The first charge and discharge and first coulomb efficiency results of the positive electrode material at 0.1C:

[0091]

[0092] It can be seen that the increase in the concentration of the precursor solution means an increase in the amount of water absorbed by the organic solvent per unit volume. If the concentration of the precursor solution is too high, the organic solvent will not be completely dehydrated, the obtained precursor elements will be unevenly distributed, and the material capacity will decrease. Considering the utilization rate of the organic solvent and the yield of the precursor, therefore, in the scheme of the present invention, it is most ideal to configure the concentration of the precursor solution to 1.2 mol / L.

[0093] The scheme of the present invention seems simple, but it is not easy to think of. Only by deeply studying the preparation characteristics of sodium iron pyrophosphate materials, combining the characteristics of raw materials, and paying creative labor, can high-performance sodium iron pyrophosphate materials be prepared in a simple and effective way, so that technology is more in line with efficiency, quality, and cost. Therefore, compared with the prior art, the technical progress of the present invention is very obvious, with outstanding substantive characteristics and significant progress.

[0094] The above-mentioned embodiments only express the specific implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the protection scope of the present invention. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A sodium iron pyrophosphate positive electrode material, characterized in that The molecular formula of the sodium iron pyrophosphate positive electrode material is Na 3.6 Fe 2.6 (PO4) 1.6 P2O7.

2. A method for preparing the sodium iron pyrophosphate positive electrode material according to claim 1, comprising the following steps: Step S1, dissolving a soluble compound containing an iron source, a sodium source, a phosphorus source, and a carbon source in deionized water to form a precursor solution with a concentration of 0.2-2.4 mol / L, and stirring until uniform; the stoichiometric ratio of the sodium source, the iron source, the phosphorus source, and the carbon source in the soluble compound is 1.33-1.50:1:1.33-1.50:1.33-1.50; Step S2, adding the precursor solution into 1-4 times the volume of a strongly water-absorbing organic solvent, stirring thoroughly to precipitate the precursor, and then filtering under reduced pressure to obtain a precursor with uniform element distribution; Step S3: sintering the precursor at high temperature to obtain sodium iron pyrophosphate positive electrode material.

3. The method according to claim 2, characterized in that The concentration of the precursor solution is 1.2 mol / L.

4. The method according to claim 2 or 3, characterized in that: The soluble compound composition comprises the following substances in a molar ratio: first soluble compound 2-3; The second soluble compound 3-4; The third soluble compound 3-4.

5. The method according to claim 4, characterized in that The first soluble compound is one or more of ferric citrate, ferric acetylacetonate, ferric nitrate, ferrous sulfate, and ferric hydroxide.

6. The method according to claim 5, characterized in that The second soluble compound is one of sodium hydroxide, sodium carbonate, sodium acetate, sodium nitrate, sodium nitrite, sodium dihydrogen phosphate, disodium hydrogen phosphate, phosphoric acid, diammonium hydrogen phosphate, and sodium pyrophosphate, which contains both a sodium source and a phosphorus source, or a combination of two or more substances which contains both a sodium source and a phosphorus source.

7. The method according to claim 6, characterized in that The third soluble compound is one or more of soluble starch, citric acid, grape, sucrose and maltose.

8. The method according to claim 2 or 3 or 5 or 6 or 7, characterized in that: The strong water-absorbing organic solvent is one or more of ethylene glycol, propylene glycol, N-methylpyrrolidone and dimethylacetamide.

9. The method according to claim 8, characterized in that In the step S2, the precursor solution is added into 2.5 times the volume of a strongly water-absorbing organic solvent.

10. The method according to claim 2 or 3 or 5 or 6 or 7 or 9, characterized in that: The step S3 comprises the following steps: Step S301, pre-calcining the precursor at 300° C.-350° C. in an inert atmosphere for 5-6 hours to obtain an intermediate product; Step S302: calcining the intermediate product at 500° C.-550° C. in an inert atmosphere for 15-18 hours to obtain a sodium iron pyrophosphate positive electrode material.

Citation Information

Patent Citations

  • Polyanionic sodium ion battery positive electrode material and preparation method thereof

    CN110226252A

  • Preparation method of lithium iron phosphate cathode active material

    CN112086635A

  • Preparation method of doped modified sodium ferric pyrophosphate positive electrode material

    CN115133023A

  • Carbon-coated ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof

    CN116230923A

  • Preparation method of high-performance sodium ion battery positive electrode material Na4Fe3 (PO4) 2P2O7

    CN117585658A

Cited By

  • Composite polyanion positive electrode material and preparation method and application thereof

    CN122224803A